Sound Symbolism - Freya Young (Groundings, 2016)
Over 100 years ago Swiss linguist Ferdinand de Saussure proposed that, aside from onomatopoeia, there is no logical relationship between words and their meanings. This article aims to gather and analyse the mounting evidence that has emerged over the last century that overrules this assertion. From the books we escape to, to the inescapable marketing language surrounding us; from the names we call our children, to how children learn language: sound symbolism pervades everyday life in more ways than is probably realised. It becomes apparent that the mind’s perception of meaning may be influenced by the sounds of words themselves. By consequence, it seems that some of the roots of language may not be as illogical as Saussure thought; this article considers the possibility of there being a neurological explanation behind ‘sound symbolism’.